2006
DOI: 10.1063/1.2190463
|View full text |Cite
|
Sign up to set email alerts
|

Modulated optical transmission of subwavelength hole arrays in metal-VO2 films

Abstract: We demonstrate the modulation of the transmission of near-infrared light through a periodic array of subwavelength apertures in Ag–VO2 and Au–VO2 double-layer films using the semiconductor-to-metal phase transition in VO2. The transmitted intensity ratio increases by a factor of 8 as the VO2 goes from the semiconductor to the metal phase. We attribute this modulation to the switchable dielectric-permittivity contrast between the air-filled holes in the array and the surrounding VO2 material, a conjecture that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
58
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 22 publications
1
58
0
Order By: Relevance
“…This possibility has been but sparsely explored, with only a few reports appearing regarding the effect of temperature on the plasmon resonance of Ag or Au nanospheres embedded in a VO 2 matrix [16][17][18], of composite Au-VO 2 films [19] or of VO 2 @Au (Auon-VO 2 ) core-shell particles [20]. Curiously, however, the possibility of self-regulating temperature control in these structures appears to have been hitherto overlooked.…”
mentioning
confidence: 99%
“…This possibility has been but sparsely explored, with only a few reports appearing regarding the effect of temperature on the plasmon resonance of Ag or Au nanospheres embedded in a VO 2 matrix [16][17][18], of composite Au-VO 2 films [19] or of VO 2 @Au (Auon-VO 2 ) core-shell particles [20]. Curiously, however, the possibility of self-regulating temperature control in these structures appears to have been hitherto overlooked.…”
mentioning
confidence: 99%
“…This might be partially ascribed to the relative difficulty in obtaining sub-wavelength metal patterns, especially in the visible range [6]. VO 2 is very commonly used for SP thermal tuning investigations [4,5,7], due to the large variation of refractive index (∼2.8 at room temperature and ∼2.2 at 80°C at 600 nm [8]) induced by the metal-insulator phase transition around 65°C. For preparation of large-area patterns with nano-scale resolution, physical (plasma) etching is usually used, which often requires a metallic sacrificial mask.…”
Section: Introductionmentioning
confidence: 98%
“…Alternative nanofabrication routes have to be used to generate the desired patterns. For example, Suh et al reported thermally modulated extraordinary transmission in Ag/VO 2 hole arrays prepared by focus ion beam etching [7].…”
Section: Introductionmentioning
confidence: 99%
“…In parallel with the advances in the generation of nanostructures with their interesting electronic [1], chemical [2][3][4], and optical properties [5][6][7][8], the possibility arose to investigate and use the matter-light interaction on the nanoscale. A very promising route to overcome the diffraction limit and to focus light on the nanometer scale is plasmonics on metallic nano-objects.…”
mentioning
confidence: 99%